Representative democracy in flux : deconstructive narratives from a legal and constitutional perspective - Belov, Martin (Routledge, 2025)
"This book delves into the core of representative democracy in order to explain its main features - institutional and imaginary - and to show the reasons for its increasing dysfunctionality. The collection explores the constitutional imaginaries of representation. It outlines the main factors influencing the failures of representative democracy, in an age of constitutional crisis and transition, being gradually deconstructed via tendencies towards authoritarianism and technocracy. Special attention is devoted to the impact of the politics of fear on representative democracy. The analysis shows the main challenges stemming from national, international, transnational, and supranational technocracy produced by the increased role of administration, agencies, and courts. It exposes representative democracy as a composite phenomenon stretched between reason and emotions and between the constitutional past, present, and future. The volume will be of interest to researchers, academics, and policy-makers working in the areas of Constitutional Law and Politics, Comparative Constitutional Law, Administrative Law, Human Rights Law, and Theory and Philosophy of Law"-- Provided by publisher.
Keywords: Constitutional law.; Democracy.; Constitutional law -- Philosophy.; elektronické knihy; electronic books